Manières de penser dans l'antiquité mediterranéenne et orientale: mélanges offerts à Francis Schmidt par ses élèves, ses collègues et ses amis - Schmidt, Francis ca. 20./21. Jh.; Batsch, Christophe; Vârtejanu-Joubert, Mădălina (Journal for the study of Judaism, 2009)
An accurate picture of ancient religious studies: all papers stress historiography, anthropological history, and philology. Topics range from Mesopotamia to Christianism and rabbinic Judaism. The result is to offer an ambitious and comparatist status quaestionis for today